AB1105 A NOVEL AUTOINFLAMMATORY AND LYMPHOPROLIFERATIVE SYNDROME ASSOCIATED WITH PIM1 MUTATIONS. (June 2019) - Ferrara, Giovanna; Polizzi, Silvio; Valencic, Erica; Chiocchetti, Annalisa; Vuch, Josef; Pin, Alessia; Piscianz, Elisa; Vozzi, Diego; Pastore, Serena; Tomietto, Paola; Taddio, Andrea; Faletra, Flavio; et al.
Abstract : Background: Whole exome sequencing can allow genetic diagnosis in subjects with long lasting clinical stories not supporting any well-defined disorder. A 35-year-old man was referred to ophthalmologist's evaluation for blurry vision in his left eye. The fundus examination showed choroidal lesions in both eyes. His past medical history was relevant for celiac disease, recurrent episodes of fever and skin rashes with leukocytoclastic vasculitis, inflammatory lesions of the osteoarticular and muscular system, one episode of aseptic meningitis, an intracranial granuloma and two episodes of anterior uveitis. He had also splenomegaly with non-caseating granulomas. Brain TC founded multiple lytic and sclerotic skull lesions. He was diagnosed with atypical sarcoidosis and treated with oral steroid and methotrexate. Laboratory data always showed elevated erythrocyte sedimentation rate, strong positive C-reactive protein and polyclonal gammopathy. Objectives: To describe functional and genetic data supporting the role of a PIM1 mutation in the multisystemic inflammation and lymphoproliferation of the patient. Methods: Whole exome sequencing (WES) analysis. Flow-cytometry to evaluate Pim1 expression, Bad phosphorylation (target of Pim1 kinase) and the effect of PIM inhibitor on peripheral blood mononuclear cell (PBMC) viability. RNAseq was on primary fibroblasts from the patient and from healthy donors. Cloning of the mutated gene in a vector for further functional studies. Results: WES analysis revealed the de novo heterozygous missense variation c.C1132A (p.H378N) in PIM1 gene. This variation was never described in on-line database and was predicted as damaging by various bioinformatic tools. Preliminary functional investigations in fibroblasts showed normal expression of Pim1, but higher phosphorylation of BAD protein was measured in cells from the patient. Moreover, PBMC from the patient displayed a lower sensitivity to the PIM inhibitor PIM447. RNAseq showed an altered expression profile in genes involved in the extracellular matrix organization. Conclusion: PIM1 is an oncogene that encodes a protein kinase and, indeed, somatic gain of function mutations can be found in cancers. Preliminary data obtained from our patient suggest a gain of function effect of the p.H378N variant. The lymphoproliferative disorder may be sustained by the anti-apoptotic action of phosphorylated BAD. Recent data correlated hyperactive PIM1 in tumors with high degree of inflammatory infiltration accompanied by NFAT and mTOR activation and IL6 expression. A role of this cytokine also in our patient was coherent with a good clinical response to a treatment with tocilizumab, targeting IL-6. Although these results are supportive of a role of mutated PIM1 in the observed phenotype, we cannot still claim that this is causative of a novel syndrome. The detection of further cases and functional studies on cells transfected with mutated PIM1 will help shedding more light on this inflammatory and lymphoproliferative disorder. Disclosure of Interests: None declared